Sixteen new records for the flora of Lebanon - Addam, Khodr; Bou-Hamdan, Mounir; Sabbagh, Nisreen (Current Botany, 2020)
Significant new species that belong to diverse genera and families were recorded to exist in Lebanon during our continuous non-stop field survey all over the country. The authors gathered some exceptional taxa from distinctive locations and habitats of the country, which were not reported so far in the flora documentation with the exception of Quercus libani, that is regarded as a very atypical species (for Lebanon) discovered for the first time after Post in 1932. The current paper deals with the records Anchusa milleri Lam. ex Spreng, Bassia hyssopifolia (Pall.) Kuntze., Eminium heterophyllum (Blume) Schott., Euphorbia prostrata Aiton, Euphorbia serpens Kunth, Hypericum olivieri (Spach) Boiss., Kickxia cirrhosa (L.) Fritsch., Lamium macrodon Boiss. & A.Huet, Onosma fruticosum Sm.lder, Plantago crypsoides Boiss., Platanthera holmboei H.Lindb., Potamogeton perfoliatus L., Quercus libani G.Olivier, Rhamnus kurdica Boiss. & Hohen., Tulipa biflora Pall. and Xanthium strumarium subsp. sibiricum (Patrin ex Widder) Greuter. The plants were photographed, collected, dried and herbarium specimens were prepared and deposited in K. Addam's Herbarium AUL University (Lebanon). Their taxonomical and ecological characters as well as their geographical distributions were exhibited. New Taxa (representing 14 genera in 12 families of flowering plants) were recognized with the reference of different floras and recent literature for their authentication. The present study also files them with updated nomenclature, descriptions, and notes on phenology and images for their easy identity.